Sustainable fin fish farming on islands, the example from the Faroe Islands. ... - Knud Simonsen, Gunnvør á Norði (ASC 2014 - Theme session K, 2023)
No abstracts are to be cited without prior reference to the author. Outbreaks of Infectious Salmon Anaemia (ISA) caused a dramatic declination in the production from 52.000 tonnes gutted weight in 2003 to 15.600 tonnes in 2006 in the salmonid fish farming industry in the Faroe Islands. This motivated a restructuring of the industry. New management practices and regulations were developed, where the main elements are zonation, single year classes, fallowing between production cycles and strict regulation of all transport. Under this new management system and a generally improvement of the husbandry the production has increased to nearly 20% above the maximum production prior to the ILAcrisis, but from 25% fewer smolts. However, increasing abundance of sea lice are a growing challenge, and adjustments in the management are expected. ...